Prevalence of anemia and iron deficiency anemia in Chinese pregnant women (IRON WOMEN): a national cross-sectional survey - Jing Tan; Guolin He; Yana Qi; Hongmei Yang; Yiquan Xiong; Chunrong Liu; Wen Wang; Kang Zou; Andy H. Lee; Xin Sun; Xinghui Liu (BMC, 2020)
Abstract Background The current evidence about anemia and iron deficiency anemia (IDA) during pregnancy remains elusive in China. The purpose of this study is to investigate the prevalence of anemia and IDA and their risk factors in Chinese pregnant women. Methods A nationwide cross-sectional survey of pregnant women was conducted during their antenatal visits. Using a multi-stage sampling method, 24 hospitals from 16 provinces across China were selected. Structured questionnaires were administered to collect information from participants and to extract clinical data from electronic medical records. Mixed-effects logistic regression models were performed to determine the risk factors associated with anemia and IDA. Results In total, 12,403 pregnant women were enrolled, including 1018 (8.2%) at the first trimester, 3487 (28.1%) at the second, and 7898 (63.7%) at the third. Overall, 19.8% of women were diagnosed with anemia and 13.9% were diagnosed with IDA. The prevalence of anemia and IDA varied among regions and increased by gestational month, peaking at the eighth gestational month (24.0% for anemia and 17.8% for IDA). Pregnant women at advanced stage of gestation, non-local residents, multiple gestations, multiparity, pre-pregnancy underweight, and those experiencing severe nausea or vomiting during pregnancy, were associated with higher risks of anemia and IDA. Conclusions The prevalence of anemia and IDA during pregnancy are similar to those from developed countries and vary across regions in China.